Does Art Activism Affect Pre-school Children's Attitudes towards Individuals with Blindness?. Issue 2 (4th March 2022) - Szubielska, Magdalena; Wojtasiński, Marcin; Pasternak, Katarzyna; Szymańska, Anna; Wójtowicz, Marzena
ABSTRACT: We tested whether viewing an exhibition of works by artists with visual impairments had a positive effect on the attitudes of children viewing it towards individuals with blindness. The study involved children ( N = 226) aged 4–6 divided into three groups: (1) who viewed the exhibition in the art gallery with a guide, (2) who viewed the exhibition in the art gallery on their own, (3) tested in a pre-school, without viewing the exhibition and without any knowledge about the exhibition (the control condition). We controlled participants' gender and their familiarity with individuals with blindness. All children were asked to assess their attitude towards the persons who are blind (using a thermometer of feelings). Moreover, the children who visited the gallery assessed to what extent they liked the exhibition. We showed that visual art might be a tool for social change as the young gallery visitors had more positive attitudes towards people who are blind than children who did not view the exhibition. However, art activism affected pre-school children's attitudes towards individuals with blindness only when young visitors explored the exhibition on their own.